1993
DOI: 10.1111/j.1558-5646.1993.tb02133.x
|View full text |Cite
|
Sign up to set email alerts
|

PHENOTYPIC PLASTICITY INPOLYGONUM PERSICARIA.II. NORMS OF REACTION TO SOIL MOISTURE AND THE MAINTENANCE OF GENETIC DIVERSITY

Abstract: Adaptive phenotypic plasticity is the predicted evolutionary response to fine‐grained fluctuation in major environmental factors, such as soil moisture in plant habitats. This study examines genotypes from two natural populations of Polygonum persicaria, one from a relatively homogeneous, moderately moist site, and one from a site in which severe drought and root flooding occur within single growth seasons. Norms of reaction (phenotypic response curves) were determined for a random sample of eight and ten clon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(21 citation statements)
references
References 51 publications
(70 reference statements)
1
20
0
Order By: Relevance
“…The direction of these significant responses was generally consistent with previous studies of plasticity in response to moisture availability (Sultan and Bazzaz 1993b;Sultan et al 1998;Heschel et al 2004;Heschel and Riginos 2005). However, our results do not support the hypothesis that plasticity occurring through developmental and regulatory responses is likely to be adaptive.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The direction of these significant responses was generally consistent with previous studies of plasticity in response to moisture availability (Sultan and Bazzaz 1993b;Sultan et al 1998;Heschel et al 2004;Heschel and Riginos 2005). However, our results do not support the hypothesis that plasticity occurring through developmental and regulatory responses is likely to be adaptive.…”
Section: Discussionsupporting
confidence: 80%
“…et al 1998; but see Dorn et al 2000). However, the importance of costs as a constraint on the evolution of plasticity in plants remains unclear. Physiological traits that control the uptake of carbon dioxide and loss of water are highly plastic (e.g., Sultan and Bazzaz 1993a;Sultan et al 1998;Heschel et al 2004) and key determinants of plant growth and reproduction (Ackerly et al 2000). Plasticity in physiology may be the result of reduced function and growth in response to resource limitation or developmental and regulatory responses to specific environmental cues (Pigliucci 1996).…”
mentioning
confidence: 99%
“…As an example, in one study Sultan and Bazzaz (1993a) found that Polygonum persicaria grown under flooding produced dense mats of finely branched superficial and adventitious roots at the soil surface, such that growth was maintained by avoiding the deleterious effects of oxygen deficits. In a second study (Sultan and Bazzaz 1993b), they found that at different nutrient levels, P. persicaria maintained the same photosynthetic surface area relative to total biomass and the same leaf nitrogen concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 summarizes the responses of the most common plant species at SBL. persicaria, for instance, maintained growth and reproduction at close to maximum levels when flooded; by growing superficial and adventitious roots, this species was able to avoid any oxygen deficit resulting from being underwater (Sultan and Bazzaz 1993). Three varieties of P. amphibium had similar or higher mean leaf area in a submerged treatment, as compared to controls (Mitchell 1976).…”
Section: Response Of Other Taxa To Floodingmentioning
confidence: 89%